Arthropods Diversity at Paddy Generative Phase in Rainfed Rain Field - Abdul Azis Ambar; Rudy; Harsani; Nur Ilmi (Future Science, 2022)
Arthropods are the largest phylum in the animal kingdom and are found in various ecosystems, including rainfed rice fields. This study aims to determine the diversity of arthropods and their diversity index. As well as the status of each arthropod in rainfed rice fields. The research method used is purposive random sampling, by determining the location point for arthropod sampling, which refers to the method (Sari et al., 2020). Samples were obtained by using 2 traps, namely sweep net traps, to catch active flying arthropods, or netting with a net for 10 double swings. The second is a pit fall trap, to catch arthropods on the ground. Using a beaker with a volume of 150 ml and placed parallel to the ground. The results showed that there was a diversity of arthropods of 35 species, including 28 species as natural enemies and 6 species as pests, with a diversity index of 2.91 which means that it is in the moderate category.